2014
DOI: 10.1039/c4md00055b
|View full text |Cite
|
Sign up to set email alerts
|

The biology and synthesis of α-hydroxytropolones

Abstract: α-Hydroxytropolones are a subclass of the troponoid family of natural products that are of high interest due to their broad biological activity and potential as treatment options for several diseases. Despite this promise, there have been scarce synthetic chemistry-driven optimization studies on the molecules. The following review highlights key developments in the biological studies conducted on α-hydroxytropolones to date, including the few synthetic chemistry-driven optimization studies. In addition, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 71 publications
2
40
0
Order By: Relevance
“…11 Driving these studies is the large number of therapeutically relevant targets that α-hydroxytropolones have been identified as lead compounds for, 12 and the relative scarcity of accompanying synthetic chemistry-driven structure-function studies. 13 We believe that a general, reliable, and practical de novo method to access these compounds would be instrumental in fully assessing their therapeutic potential.…”
mentioning
confidence: 99%
“…11 Driving these studies is the large number of therapeutically relevant targets that α-hydroxytropolones have been identified as lead compounds for, 12 and the relative scarcity of accompanying synthetic chemistry-driven structure-function studies. 13 We believe that a general, reliable, and practical de novo method to access these compounds would be instrumental in fully assessing their therapeutic potential.…”
mentioning
confidence: 99%
“…We previously demonstrated that numerous compounds selected for the capacity to suppress HIV or HBV RNase H activity or close chemical relatives of these compounds also inhibit HSV replication in cell cultures (33). One of these compounds, the natural product ␤-thujaplicinol (34), is the most widely studied member of a class of troponoids called ␣-hydroxytropolones that have been identified as anticancer agents (35,36) as well as lead therapeutic agents for a number of infections, including HIV (37)(38)(39)(40)(41), HBV (42), malaria (43), and many bacteria (44). This antimicrobial activity is often attributed to the capacity of the compounds to sequester divalent cations in the active sites of dinuclear metalloenzymes, a feature arising from the three contiguous oxygen atoms on the troponoid ring (45)(46)(47).…”
mentioning
confidence: 99%
“…2427 Three recent reviews focused on special classes of compounds, such as colchicine, 28 the five tropones derived from the Cephalotaxus species, 29 and α-hydroxytropolones (dihydroxytropones). 30 …”
Section: Introductionmentioning
confidence: 99%